Smartphone addiction percentage among dental student during COVID-19 pandemic: a cross-sectional study - Siregar, Darmayanti; Munthe, Sri Apriyanti; Harahap, Rahmadhani; Nasution, Fitri Anisah; Taruna, Muhammad (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: During COVID-19 pandemic, smartphones can be used as media of an effective learning, information center, communication, and as a device to increase students’ knowledge. Many advantages can be obtained by using a smartphone during distance learning. However, excessive use of smartphones may also lead to many disadvantages. The users have become dependent on the features provided by smartphones. Consequently, they will experience anxiety if they do not use their smartphone for too long. This condition is called smartphone addiction. The aim of study is to determine the percentage of smartphone addiction among dental students during COVID-19 pandemic. Methods: This study was utilizing the cross-sectional design and random sampling technique. The questionnaires of Smartphone Addiction Scale-Short Version (SAS-SV) were distributed using Google Forms and then analyzed using Microsoft Excel. The total number of respondents included in the inclusion criteria was 289 active students, and they were willing to participate in this study. Results: The majority of respondents (33,9%) agreed that they have lost time completing their assignments due to smartphone use, while the least respondents (29,1%) disagreed that people around them used smartphones too often. The majority of the respondents claimed to have smartphone addiction (88,2% male, 76,5% female). Conclusion: The majority of respondents are experiencing smartphone addiction. Further education regarding the early symptoms of smartphone addiction is required among dental students in order to control smartphone use according to their needs.